Communication skills and mathematical disposition in implementing geogebra-assisted problem-based learning strategies - Christina Khaidir; Rozi Fitriza; Ninik Yumariza; Rahmatul Wahid (Fakultas Tarbiyah Universitas Ibrahimy, 2024)
This paper aims to determine students' communication skills and mathematical disposition in implementing problem-based learning strategies using the Geogebra application. This type of research was a quasi-experiment with a control group design. The subjects of this research were classes A and B. The population in this research was all students in the odd semester 2023/2024 who were taking the Plane and Space Geometry course, which consists of two classes that were tested using the t-test with data from the student's final test. Based on calculations of the results of students' mathematical communication skills, specifically the experimental class 81.00 and the control class 71.16. Thus, students' mathematical communication abilities in problem-based learning assisted by Geogebra were better than those in conventional education. On the other hand, the results of students' mathematical disposition abilities were 76.59 for the experimental class and 68.16 for the control class. Thus, students' mathematical disposition abilities in problem-based learning assisted by Geogebra were better than those in conventional education.